Luxembourg : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that the Luxembourg authorities are adjusting policies to the growth slowdown, although major new initiatives are on hold in the run-up to the June 2004 general election. Tax cuts, high expenditure, and weak activity are estimated to have caused a general government deficit in 2003. Executive Directors have welcomed indications that real GDP growth is rebounding, following an unusually long period of sluggish activity. However, they have stressed that medium-term growth prospects are now less buoyant in comparison with the exceptional growth performance of the past decade.